Fecal microbiota profiling in organic and conventional dairy farms differing in farm-level somatic cell counts and raw milk bacterial infections - Kim, Sung Jae; Ro, Younghye; Lee, Geun-Shik; Kizaki, Keiichiro; Kimura, Atsushi; Kim, Yo-Han (Frontiers in Veterinary Science, 2026)
This study investigated the fecal bacterial communities in commercial dairy farms with varying milk quality, defined by differences in somatic cell counts, to elucidate their association with productive performance and the presence of intramammary bacterial infections. Four dairy farms, selected to represent diverse management environments, included one organic farm (OF) and three conventional farms (CF1, CF2, and CF3), with comparable parity ranges and days in milk, while somatic cell counts across farms ranged from 52.9 to 390.3 × 103 cells/mL. Fecal bacterial community analysis identified 13 phyla and 190 genera, among which Order Lachnospirales (o_Lachnospirales), genus UCG-010 (g_UCG-010), and genus Rikenellaceae RC9 gut group (g_Rikenellaceae_RC9_gut_group) showed the highest linear discriminant analysis (LDA) scores in OF, CF2, and CF3, respectively. Predicted functional pathway analysis of the fecal bacterial community identified 19 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways with significant differences. The pathway ‘various types of N-glycan biosynthesis’ (ko00513), which may be associated with immune activity in cows, was most upregulated in CF2, whereas ‘steroid biosynthesis’ (ko00100), related to fat metabolism in the rumen, was most downregulated in CF3 compared to OF. Correlation analyses of shared core taxa and milk parameters revealed that g_Rikenellaceae_RC9_gut_group, g_UCG-010, and g_UCG-005, which are closely linked to cellulose digestion and energy metabolism, showed significant correlations with milk urea nitrogen and milk protein content. Among the KEGG pathways, indole alkaloid biosynthesis (ko00901) and betalain biosynthesis (ko00965), both associated with gut health, were positively correlated with milk yield. Subclinical mastitis infection rates ranged from 27.8 to 58.1% per farm and 9.72 to 25.6% per quarter, with Staphylococcus chromogenes being the most prevalent bacterial isolate, followed by S. aureus, S. simulans, and S. epidermidis. Farm-level similarity and dissimilarity analyses revealed statistically significant differences in fecal bacterial community structures, predicted functions, and distributions of raw milk bacterial infections. These findings indicate that the distribution and functional potential of fecal bacterial communities are closely associated with milk quality parameters, whereas their composition and the distribution of intramammary pathogens are highly farm-specific, highlighting the need for further research to clarify their relationship.